2022
DOI: 10.1021/acs.jpclett.2c00583
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Generation of Coherent Phonons in Two-Dimensional Bismuthene

Abstract: Coherent phonons generated through regulation of lattice oscillation via ultrafast laser pulses or X-rays have been desired in various fields, including optoelectronics, thermal and quantum information, and communications. Phonon coherence of two-dimensional (2D) materials is particularly attractive as it enables controllable information transmission but is challenging as the weak interplanar coupling makes phonon excitation extremely difficult. Herein we managed to generate size-dependent phonon coherence fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…As a result, the interlayer force weakens, the interplanar spacing widens, and the number of crystal interfaces and defects increases. [51] This is consistent with the previous structural characterization results.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…As a result, the interlayer force weakens, the interplanar spacing widens, and the number of crystal interfaces and defects increases. [51] This is consistent with the previous structural characterization results.…”
Section: Resultssupporting
confidence: 93%
“…the bandgap. [49,51,53] In bulk Bi with very few crystal defects, most of the photogenerated carriers recombine in the bulk phase and few photogenerated electrons migrate to the surface. This is consistent with the photocurrents and photocatalytic performance.…”
Section: Resultsmentioning
confidence: 99%
“…From the corresponding Fourier transform spectra of CBM and VBM shown in Figure c, we found that the electron and hole transfer in monolayer bismuthene couple with several phonon modes less than 10 Thz, and the dominant peaks marked with red arrows around 4 Thz (∼120 cm –1 ) could be contributed to the A 1g mode of the bismuthene monolayer (opposite-in-phase out-of-plane vibrations). By introducing SiO 2 substrate, as illustrated in Figure d, the dominant peaks around 4 Hz (red arrows) increase significantly and this enhancement can be explained by the coherent phonons of both bismuthene (A 1g mode) and α-quartz (A 1 and E modes). , The next peaks ranging from 13 THz (∼450 cm –1 ) to 35 THz (∼1180 cm –1 ) are associated with the phonon modes of α-quartz, where the peaks at ∼450 cm –1 and ∼967 cm –1 (blue arrows) correspond to the A 1 and E modes of α-quartz, and the peak at ∼1180 cm –1 (gray arrows) can be assigned to the E modes. Clearly, the hole transfers at the main peak (∼4 THz) for both bismuthene and bismuthene/SiO 2 are faster than the electron transfers.…”
mentioning
confidence: 99%
“…The frequencies around the red arrow may originate from the A 1g mode of bismuthene and A 1 , E modes of α-quartz. The blue arrows indicate the nearby frequencies could come from A 1 , E modes of α-quartz, while the gray arrow indicates that the surrounding frequencies might be caused by only E modes of α-quartz. , …”
mentioning
confidence: 99%
“…Due to a sound-like dispersion, the modes found here cannot be probed directly in the optical experiments. However, in the nanostructures they can become optically active like it is largely exploited in the graphene plasmonics. Another possibility might consist of employing optical means in a way similar to that employed for measuring the whole phonon dispersion. …”
mentioning
confidence: 99%